TRAINING AND MENTORING IN MAKING BEETROOT FOOD AND DRINKS TO PREVENT CANCER - Mega Indah Puspita; Sugiyanto Sugiyanto; Gatot Murti Wibowo; Susi Tri Isnoviasih; Gharis Sabrina Nur Fitri; Tamanda Rahmi; Priska Puspa Sari; A May Twenty Natalie Solecha; Irna Norita Sari (Poltekkes Kemenkes Semarang, 2025)
Beetroot, also known as Beta Vulgaris L, is a type of tuber plant that is reddish purple in color and has a shape similar to a potato. The pigment found in red beets is betalain, betalain is a class of antioxidants. Betacyanin is classified as an antioxidant that can prevent cancer, Cancer is one of the most devastating diseases affecting many people around the world. It is characterized by the uncontrolled growth of abnormal cells in the body, which can spread to other tissues through a process called metastasis. Beetroot has been linked to various health benefits, including its ability to fight cancer. However, public knowledge and understanding of the benefits of beetroot and how to cook it creatively and enjoyably is still limited.The solution is provided through training and mentoring for the community in making foods and beverages containing beetroot, ranging from practical training sessions to creating recipes that are easy to understand and follow. method of providing material on the importance of beetroot for preventing cancer as well as training and mentoring or hands-on in making beetroot juice and pudding.This community service activity was held at the Dinar Indah Cluster, RT 04 RW 26 Meteseh, Tembalang, with 30 participants. The activity included providing information on the importance of beetroot in preventing cancer. Community service activities also involve hands-on activities involving making beetroot juice and pudding by participants. Based on the results of the comparison between the pre-test and post-test, there was a significant increase between the scores of 40-60 to 80-100. This increase in scores indicates that the participants' understanding of beetroot, starting from the scientific aspects, nutritional content, to its role in cancer prevention, has experienced a real increase, and 100% of participants stated that the benefits of beetroot are very good for preventing cancer and encouraging people to adopt healthy behavior by diligently consuming beetroot.